Associations of equol‐producing status with white matter lesion and amyloid‐β deposition in cognitively normal elderly Japanese. Issue 1 (22nd October 2020) - Sekikawa, Akira; Higashiyama, Aya; Lopresti, Brian J; Ihara, Masafumi; Aizenstein, Howard; Watanabe, Makoto; Chang, Yuefang; Kakuta, Chikage; Yu, Zheming; Mathis, Chester; Kokubo, Yoshihioro; Klunk, William; et al.
Abstract: Introduction: Equol, a metabolite of a soy isoflavone transformed by the gut microbiome, is anti‐oxidant and anti‐amyloidogenic. We assessed the associations of equol with white matter lesion normalized to total brain volume (WML%) and amyloid beta (Aβ) deposition. Methods: From 2016 to 2018, 91 cognitively normal elderly Japanese aged 75 to 89 underwent brain magnetic resonance imaging and positron emission tomography using 11 C‐Pittsburgh compound‐B. Serum equol was measured using stored samples from 2008 to 2012. Equol producers were defined as individuals with serum levels >0. Producers were further divided into high (> the median) and low (≤ the median) producers. Results: The median (interquartile range) WML% was 1.10 (0.59 to 1.61); 24.2% were Aβ positive, and 51% were equol producers. Equol‐producing status (non‐producers, low and high) was significantly inversely associated with WML%: 1.19, 0.89, and 0.58, respectively (trend P < .01). Equol‐producing status was not associated with Aβ status. Discussion: A randomized‐controlled trial of equol targeting WML volume is warranted.